Rekonstruksi Pengaturan Pemberian Honorarium Tim Pelaksana Kegiatan dalam Standar Harga Satuan Regional untuk Kepastian Hukum: Reconstructing Honorarium Arrangements for The Activity Implementation Team Within The Regional Unit Price Standard to Ensure Legal Certainty - Yudaperwira, Iqbal (SHARE Journal, 2025)
The government issued the Regional Unit Price Standard (SHSR) through Presidential Regulation No. 33 of 2020, providing guidance for regional governments in planning and budgeting. However, in practice, discrepancies exist in applying the SHSR, particularly concerning honorariums for the Activity Implementation Team. This study analyzes the specific provisions within the SHSR that govern honorariums for the Activity Implementation Team. A normative juridical method was employed, utilizing both statutory and conceptual approaches to examine honorarium payments. Findings indicate that the SHSR contains unclear provisions regarding how honorarium payments for implementing officials are classified. This ambiguity creates legal uncertainty in applying these provisions. According to principles of legislative drafting, clarity  in regulatory formulation is fundamental for effective legislation. In accordance with the Single Principle of legislative interpretation, the provision of honorarium for the Activity Implementation Team shall not be determined by the number of team members, but rather by the number of teams eligible for such honorariums. To ensure legal certainty, the regulations governing these honorariums must be revised to establish a clearer and more appropriate normative language. Such reconstruction should clarify criteria for selecting eligible Activity Implementation Teams,  and set standards for honorariums  payable to regional heads and deputy regional heads.